2019
DOI: 10.1016/j.parkreldis.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional network topology correlates with clinical measures in very early-stage, drug-naïve Parkinson's disease

Abstract: Introduction:The aim of the study was to identify abnormalities of whole-brain network functional organization and their relation to clinical measures in a well-characterized, multi-site cohort of very early-stage, drug-naïve Parkinson's Disease (PD) patients.Methods: Functional-MRI data for 16 healthy controls and 20 very early-stage, drug-naïve patients with PD were obtained from the Parkinson's Progression Markers Initiative database after controlling for strict inclusion/exclusion imaging criteria. Connect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…In several recent publications on suitable sample sizes for functional neuroimaging studies using graph theory analysis, it has been found that a group size of approximately 20 is sufficient (Gargouri et al, 2016;Sreenivasan et al, 2019). (Fazekas, Chawluk, Alavi, Hurtig, & Zimmerman, 1987).…”
Section: Sample Size and Statistical Analysesmentioning
confidence: 99%
See 2 more Smart Citations
“…In several recent publications on suitable sample sizes for functional neuroimaging studies using graph theory analysis, it has been found that a group size of approximately 20 is sufficient (Gargouri et al, 2016;Sreenivasan et al, 2019). (Fazekas, Chawluk, Alavi, Hurtig, & Zimmerman, 1987).…”
Section: Sample Size and Statistical Analysesmentioning
confidence: 99%
“…In several recent publications on suitable sample sizes for functional neuroimaging studies using graph theory analysis, it has been found that a group size of approximately 20 is sufficient (Gargouri et al, 2016;Sreenivasan et al, 2019). Finally, the partial correlation coefficient was used to analyze the correlations between the ROIs that showed intergroup differences and both the cognitive domains (neuropsychological assessment composites) and the clinical variables (duration and severity of disease) in ET patients, controlling the effect of age and sex.…”
Section: Sample Size and Statistical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…These analyses have shown significant changes in the global efficiency, local efficiency and clustering coefficient in the whole brain [2,26] or within specific networks in PD patients [36,39,64]. Changes in the nodal network topology of prefrontal and supplementary motor areas as well as the striatum and thalamus [16,38,55,67] have also been reported in PD patients, sometimes in association with clinical measures [37,56].…”
Section: Introductionmentioning
confidence: 87%
“…fMRI revealed altered functional connectivity in cortical and subcortical regions, particularly in striatum, of PD patients (Hacker et al, 2012). These alterations occurred very early and were not associated with tremor manifestation, but varied depending on disease stage, PD subtype, and pharmacological treatment (Sreenivasan et al, 2019). The main problem of this application in rodents is represented by the small size of the mouse and rat brains.…”
Section: Pet Imaging Of Other Neuronal Targetsmentioning
confidence: 99%